2011
DOI: 10.4111/kju.2011.52.9.642
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Randomized Controlled Trials Published in the Korean Journal of Urology Over the Past 20 Years

Abstract: PurposeBecause low-quality trials may lead to erroneous conclusions, quality assessments are necessary. Thus, in this study, we scrutinized randomized controlled trials (RCTs) published in the Korean Journal of Urology (KJU) to assess their quantity and quality.Materials and MethodsUpon extracting RCTs from all articles published in the KJU from 1991 to 2010, assessments were made on the basis of the Jadad scale and the adequacy of allocation concealment. The selections and assessments were performed independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Lee et al [11] previously analyzed the quality of RCTs published in the Korean J Urol. According to their study, there were 28 RCTs out of 3,156 original articles presented from 1991 to 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [11] previously analyzed the quality of RCTs published in the Korean J Urol. According to their study, there were 28 RCTs out of 3,156 original articles presented from 1991 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al [11] analyzed all RCTs published in the Korean Journal of Urology (Korean J Urol). The present study assessed the quality of urological RCTs that were conducted in Korea by using the Jadad scale, the van Tulder scale, and the CCRBT.…”
Section: Introductionmentioning
confidence: 99%
“…Scales and associates 11 reported that the number of RCTs increased over time when they compared RCTs reported by the Journal of Urology, Urology, European Urology, and British Journal of Urology International in 1996 and 2004. Lee and colleagues 12 performed a quality assessment using the Jadad scale on articles published in the Korean Journal of Urology over the past 20 years and observed an increase in the number of RCTs over time.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al19 analyzed the quality of RCTs that had been published in the Korean Journal of Urology by the Jadad scale. Twenty-eight RCTs have appeared since 1991 in the Korean Journal of Urology .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lee et al19 showed that only one article had adequate allocation concealment. In the present study, compared to Lee et al,19 the mean Jadad scale score (2.95±0.76) was higher. However, in the present study, only 1 RCT had adequate allocation concealment.…”
Section: Discussionmentioning
confidence: 99%